2011
DOI: 10.1128/iai.01152-10
|View full text |Cite
|
Sign up to set email alerts
|

Branching Network of Proteinaceous Filaments within the Parasitophorous Vacuole of Encephalitozoon cuniculi and Encephalitozoon hellem

Abstract: The microsporidia are a diverse phylum of obligate intracellular parasites that infect all major animal groups and have been recognized as emerging human pathogens for which few chemotherapeutic options currently exist. These organisms infect every tissue and organ system, causing significant pathology, especially in immune-compromised populations. The microsporidian spore employs a unique infection strategy in which its contents are delivered into a host cell via the polar tube, an organelle that lies coiled … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
3
2
2

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 46 publications
(53 reference statements)
0
8
0
Order By: Relevance
“…Many of the SWPs that have been identified in various microsporidia have posttranslational glycosylation, often involving mannosylation, which is likely important for spore wall adherence to host cells during invasion. Using various proteomic techniques additional SWPs such as SWP5 (159), SWP6 and SWP7 (L.M. Weiss manuscript in preparation) have also been identified in the Encephalitozoonidae and other putative SWPs have been identified in Nosema bombycis (160164).…”
Section: Structure and Compositon Of The Microsporidian Sporementioning
confidence: 99%
“…Many of the SWPs that have been identified in various microsporidia have posttranslational glycosylation, often involving mannosylation, which is likely important for spore wall adherence to host cells during invasion. Using various proteomic techniques additional SWPs such as SWP5 (159), SWP6 and SWP7 (L.M. Weiss manuscript in preparation) have also been identified in the Encephalitozoonidae and other putative SWPs have been identified in Nosema bombycis (160164).…”
Section: Structure and Compositon Of The Microsporidian Sporementioning
confidence: 99%
“…We have previously shown that proteins with biophysical properties similar to the polar tube proteins (PTPs) can copurify with PTPs during the polar tube fractionation procedure we developed and can be demonstrated to localize to distinct, unrelated compartments within the cell such as the spore wall and the branching proteinaceous filamentous network within the parasitophorous vacuole [14]. Here we have localized a novel protein in Enc.…”
Section: Discussionmentioning
confidence: 99%
“…cuniculi spores were harvested from culture supernatants of infected rabbit kidney cell line RK13 (American Type Cell Culture Collection, Manassas, VA), fractionated to enrich for polar tube proteins, and DTT-solubilized [14, 15], as previously described but omitting the urea wash. The lysate was analysed by nanoLC ESI-MS/MS and detected peptides were mapped to hypothetical Enc.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations